PERLINDUNGAN HUKUM HAK CIPTA DI ERA DIGITAL: ANALISIS KARYA YANG DIPUBLIKASIKAN DI E-MEDIA DAN IMPLIKASINYA - Loso Judijanto; Gingga Prananda; Herwantono; Amir Machmud; Sukron Fauzi (LPPM Universitas Ekasakti, 2024)
This study aims to analyze the legal protection of copyright for works published in e-media and the implications of these regulations. This type of research is a literature study. Literature studies involve not only collecting sources but also critical analysis of these sources, to understand the contribution made by previous studies in the context of the research being conducted. The results of this study indicate that the understanding of copyright among creators of works in e-media is still very low, where around 60% of respondents are not familiar with the applicable copyright regulations. This lack of understanding, which is caused by limited information and ambiguity regarding protected rights, causes many creators to be unaware that their works can be used without permission, thus increasing copyright infringement, such as plagiarism. Previous studies also emphasize the importance of education and increasing public awareness of copyright, given that weak law enforcement and complicated complaint procedures make creators reluctant to claim their rights. Therefore, this study recommends effective education programs, cooperation between the government, e-media platforms, and creative communities, and simplification of the complaint process, to strengthen copyright protection and support the development of the creative ecosystem in the digital era.